Symbolic Communication Ability of Prospective Physics Teacher Students - Wahyuni Wahyuni; Nuril Husna; Evendi Evendi; Rini Safitri; Siti Habsari Pratiwi (Postgraduate, University of Mataram, 2022)
Research in the field of physics education, only focuses on verbal communication such as the ability to ask questions. While communication skills are not only limited to the ability to ask questions. But there is an equally important symbolic communication. The indicators of symbolic communication in question: state the ideas of physics in the form of pictures, interpreting images into physical models, explain physical phenomena into problem solving procedures. The population in this study were all students majoring in Physics Education in the fifth semester of class 2019 and third semester of 2020, and the sample consisted of 38 students. The symbolic communication abilities of prospective physics teacher students at Samudra University are as follows:Â The indicator states physics ideas in the form of pictures, 24 people or 63.16% of students can state physics ideas in the form of pictures correctly and completely, The indicator interprets the picture into the physics model, only 1 person or 2.63% of students can connect the picture into the physics model correctly and completely, Indicators explain physical phenomena into problem solving procedures, there are 17 people or 44.74% of students who can explain solving procedures correctly and completely